1962
DOI: 10.1063/1.1733429
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Valence Structures of Complexes of Cyclo-Octatetraene with Iron Tricarbonyl

Abstract: Structure determinations by x-ray diffraction methods indicate that Fe(CO)3 units are bonded to a butadiene type of residue in C8H8Fe(CO)3(I), and in (OC)3FeC8H8Fe(CO)3 (II), where the two Fe(CO)3 units are on opposite sides of the C8H8 ring. The dihedral C8H8 ring in (I) and the chair C8H8 ring in (II) are previously unknown and unsuspected geometries for cyclo-octatetraene. Crystals of (I) have symmetry Pnam, within experimental error, with four molecules in a unit cell defined by the paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

1967
1967
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 29 publications
1
29
0
1
Order By: Relevance
“…Our structure search in the Cambridge Structural Database (CSD) revealed a subunit in the structure of 9,9′,10,10′-tetradehydrodianthracene that resembles the (Z,E,Z,E)-COT structure (22). The CSD also contains one fascinating molecule, a di-Fe(CO) 3 complex of COT that approximates this geometry (23), but the organometallic bonding naturally changes the bonding picture. We also have not yet studied the possible products of intramolecular rearrangement [which play such an interesting role in the chemistry of the (Z,Z,Z,Z) form (14,16)] of the B isomer.…”
mentioning
confidence: 99%
“…Our structure search in the Cambridge Structural Database (CSD) revealed a subunit in the structure of 9,9′,10,10′-tetradehydrodianthracene that resembles the (Z,E,Z,E)-COT structure (22). The CSD also contains one fascinating molecule, a di-Fe(CO) 3 complex of COT that approximates this geometry (23), but the organometallic bonding naturally changes the bonding picture. We also have not yet studied the possible products of intramolecular rearrangement [which play such an interesting role in the chemistry of the (Z,Z,Z,Z) form (14,16)] of the B isomer.…”
mentioning
confidence: 99%
“…The ligands studied here, 3,,-dimethylstyrene and the hypothetical tricarbonylferraindene, are presumably planar in the free state but undergo the same sort of gross geometrical change on formation of their tricarbonyliron comoounds that has been found for such ligands as cyclooctatetraene (Bastiansen, Hedberg & Hedberg, 1957;Dickens & Lipscomb, 1962), tropone (Cruickshank, Filippini & Mills, 1972;Dodge, 1964) and azepine (Paul, Johnson, Paquette, Barrett & Haluska, 1968;Woodhouse, Sim & Sime, 1974). (The first of each of these pairs of references refers to the geometry of the free ligand, and the second to the structure of a tricarbonyliron derivative; a complete documentation has not been attempted.)…”
Section: Gross Changes In Ligand Geometry As a Consequence Of Interacmentioning
confidence: 56%
“…Two principal products were obtained having the compositions (C8H8)Fe(CO)3 and (C8H8)Fe2(CO)G, of which the latter complex could be prepared from the former by treating it with excess iron pentacarbonyl. The binuclear iron complex (C8H8)Fe2(CO)6 had been expected from the reaction, but the "chair" conformation (XXXV), which was subse quently found for this substance, was entirely unexpected (65,66,67). In this complex, each end of the cyclooctatetraene ligand behaves as a butadiene-type (n = 4) ligand, and bond distance measurements indicate very little w-w interaction between the two halves of the ring.…”
Section: Organotransition Metalsmentioning
confidence: 80%
“…Subsequently, Dickens and Lipscomb (65,66,67) conducted an x-ray analysis of this complex and found that the cyclooctatetraene ligand pos sessed a novel "dihedral" conformation (XXXVI). The Fe(CO)3 group is bound to only one-half of the ring, and this portion of the complex is similar to the geometry in butadiene-iron tricarbonyl.…”
Section: Organotransition Metalsmentioning
confidence: 99%